2011
DOI: 10.1292/jvms.11-0197
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Cystadenoma in a Maltese Dog: Clinical and Diagnostic Findings

Abstract: ABSTRACT. A 14-year-old Maltese dog presented for complete medical examination due to intermittent vomiting and diarrhea observed during the previous two days. A single, solitary, lobulated cystic mass was observed in the liver upon ultrasonographic and computed tomographic examination. After surgical hepatic resection to remove the mass, histological examination revealed a multilocular cyst lined by cuboidal to columnar epithelial cells, which is consistent with biliary cystadenoma. Here, we report the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…In addition, papillary projections were seen within lumen of cyst (Figure 9). The microscopic findings coincided with earlier reports of cystadenoma in dogs and biliary cystadenomas were reported as rare cystic tumors arising from liver and less commonly in extrahepatic biliary system in cases of dogs [30][31].…”
Section: Cystadenomasupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, papillary projections were seen within lumen of cyst (Figure 9). The microscopic findings coincided with earlier reports of cystadenoma in dogs and biliary cystadenomas were reported as rare cystic tumors arising from liver and less commonly in extrahepatic biliary system in cases of dogs [30][31].…”
Section: Cystadenomasupporting
confidence: 90%
“…One case of cystadenoma was diagnosed, and on ultrasonographic examination presence of mixed echotexture and congested liver along with multiple hypoechoic nodules seen throughout parenchyma of one hepatic lobe (Figure 8). Similar type of ultrasonographic findings has been reported in dogs having cystadenoma [30].…”
Section: Cystadenomasupporting
confidence: 87%
“…According to the current literature (Moon et al 2011), a dog cholangioma, in the absence of stroma, could phylogenetically evolve towards possible malignant forms. This is in contrast to the situation in humans, where stroma is evident and cases of malignant behaviour are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, this neoplasm is frequently described in cats (Adler and Wilson 1995;Trout et al 1995;Nyland et al 1999;Kristick et al 2010), whereas it has on rare occasion been reported in pigs (Graw and Berg 1977), sheep (Watt 1970) and dogs (Trigo et al 1982;Akkoc et al 2009;Moon et al 2011); moreover, in humans it is a rare tumour with a higher incidence in women older than 40 years (Ishak et al 1977).…”
mentioning
confidence: 99%